Three-dimensional tomographic analysis of the dimensions of the nasal cavity and the nasal and upper pharyngeal airway space of subjects undergoing surgically assisted maxillary expansion (Research, Society and Development, 2021)
The main objective of the surgically assisted rapid maxillary expansion (SARME) is to increase the transversal dimension of the upper dental arch in individuals with maxillary atresia. Its effects are not restricted to the maxilla, also acting on the nasal cavity and pharyngeal airway. The present study aimed to evaluate the occurrence of dimensional changes in the nasal cavity and nasal and upper pharyngeal airway space in individuals submitted to surgically assisted maxillary expansion using 2 different osteotomies. Nasal and pharyngeal airway space structures were analyzed by pre-and post-operative cone beam computed tomography scans of 29 adult subjects submitted to surgically assisted maxillary expansion. Volumetric measurement of the nasal and upper pharyngeal airway and linear measurements of the nasal cavity were performed using Dolphin Imaging 11,7 software. The data were tabulated and submitted to statistical analysis by ANOVA analysis of variance and Tukey test (p